Sex differences in the coexpression of prokineticin receptor 2 and gonadal steroids receptors in mice - Cisneros-Larios, Brenda; Elias, Carol Fuzeti (Frontiers in Neuroanatomy, 2023)
Loss-of-function mutations in prokineticin 2 (PROK2) and the cognate receptor prokineticin receptor 2 (PROKR2) genes have been implicated in reproductive deficits characteristic of Kallmann Syndrome (KS). Knock out of Prokr2 gene produces the KS-like phenotype in mice resulting in impaired migration of gonadotropin releasing hormone (GnRH) neurons, olfactory bulb dysgenesis, and infertility. Beyond a developmental role, pharmacological and genetic studies have implicated PROKR2 in the control of the estrous cycle in mice. However, PROKR2 is expressed in several reproductive control sites but the brain nuclei associated with reproductive control in adult mice have not been defined. We set out to determine if ProkR2 neurons in both male and female mouse brains directly sense changes in the gonadal steroids milieu. We focused on estrogen receptor α (ERα) and androgen receptor (AR) due to their well-described function in reproductive control via actions in the brain. We found that the ProkR2-Cre neurons in the posterior nucleus of the amygdala have the highest colocalization with ERα and AR in a sex-specific manner. Few colocalization was found in the lateral septum and in the bed nucleus of the stria terminalis, and virtually no colocalization was observed in the medial amygdala. Our findings indicate that the posterior nucleus of the amygdala is the main site where PROKR2 neurons may regulate aspects of the reproductive function and social behavior in adult mice.